(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In artice the basic features of partner interaction in the conditions of the higher are school are opened; partnenship characteristics as important phenomenon the subject-subject of interaction are allocated; its remedial aspect is analysed, and also comection of development of subjectivity of the student as necessary qunlily the future professional is established and establishments of partner mutual relations of all subjects of educational activity.